THE ANALYSIS OF SOCIAL ENTREPRENEURIAL INTENTION AMONG YOUNG GENERATION (STUDY CASE: STUDENT OF FACULTY OF BUSINESS PRESIDENT UNIVERSITY) - Hangka Panca Buana; Yunita Ismail Masjud (President University, 2020)
This research conducted to measure the factors that influence social entrepreneurial intention of young generation with use President University Faculty of Business students. It has three independent variables (empathy, self efficacy and exposure) and one dependent variable (social entrepreneurial intention). Quantitative research chosen as an approach and using questionnaire as a collection data instrument.The questionnaire distributed through online (google form, social media) to 557 respondents and the response received were 334 (59.96% response rate). Multiple regression used to analyze the data gathered. All 20 items in the questionnaire have passed the validity and reliability test by using pearsoncorrelation and cronbachalpha. Then multiple regression analysis shown that all independent variables were significance influence to dependent variable. From three independent variables, the self efficacy as the highest influence towards social entrepreneurial intention (39.7%), followed by exposure (34.4%) and empathy (25.3%).The regression model was: Y= 1.073 + 0.253 X1+ 0.397 X2+ 0.344 X3 + e. From t-test and F-test, showed that all the independent variables (empathy, self efficacy and exposure) had significant effect towards the dependent variable (social entrepreneurial intention) and it also had simultaneously significant effect towards social entrepreneurial intention. Lastly, this research explained 40.4% variation of social entrepreneurial intention could explain by empathy, self efficacy and exposure, while the rest (59.6%) explained by other factors that was not included in this research.